2021
DOI: 10.1590/2447-536x.v27i2.2269
|View full text |Cite
|
Sign up to set email alerts
|

Biology and bulb production of Eleutherine bulbosa (Iridaceae), a native species from Borneo, Indonesia

Abstract: Eleutherine bulbosa is a known ornamental plant of the Iris family, which originated from Central Borneo, Indonesia. The bulbs of E. bulbosa have long been used as a medicinal source by the local people of Borneo. Despite its known medicinal and other values, studies on the morphology and efficiency in bulb production of this species are limited. The aims of our study are to examine the vegetative and reproductive morphology of E. bulbosa, and to determine the effect of various dosages of NPK fertilizer on flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Results in in Figure 2 also indicated that, under the same level of PGRs, raising the fertilization rate resulted in steady and significant increase in flowering parameters compared to control, Accordingly, the highest values were registered by the highest rate (6 g plant -1 ), whereas the lowest values were obtained from control. The obtained increase in flowering parameters as a result of fertilization treatments is quite in line with those obtained by previous reports including Mumtaz et al (2017) on Rosa Gruss-anteplitz; Ashour et al (2018) on Euryops pectinatus; Wiendi et al (2021) on Eleutherine bulbosa.…”
Section: Flowering Parameterssupporting
confidence: 92%
“…Results in in Figure 2 also indicated that, under the same level of PGRs, raising the fertilization rate resulted in steady and significant increase in flowering parameters compared to control, Accordingly, the highest values were registered by the highest rate (6 g plant -1 ), whereas the lowest values were obtained from control. The obtained increase in flowering parameters as a result of fertilization treatments is quite in line with those obtained by previous reports including Mumtaz et al (2017) on Rosa Gruss-anteplitz; Ashour et al (2018) on Euryops pectinatus; Wiendi et al (2021) on Eleutherine bulbosa.…”
Section: Flowering Parameterssupporting
confidence: 92%
“…2). The bulb is oval and consists of many layers like a regular onion with a striking deep reddish color (Wiendi et al 2012). M. charantia, also known as karela, bitter gourd, or bitter melon, is a fruit from Cucurbitaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…The bulbs have a purplish red color with a bitter taste. The Dayak people (Borneo natives) have been using for generations the bulbs as traditional medicines [14]. Dayak people usually process it by slicing it thinly and drying it, then brewing it with boiled water.…”
Section: Bawang Dayak (Dayak Onion)mentioning
confidence: 99%